Population structure and linkage disequilibrium in diploid and tetraploid potato revealed by genome‐wide high‐density genotyping using the SolCAP SNP array. Issue 6 (3rd October 2013) - Stich, Benjamin; Urbany, Claude; Hoffmann, Per; Gebhardt, Christiane; Léon, J.
Abstract Genome‐wide association (GWA) mapping in potato requires high‐density genotyping. With the Illumina SolCAP potato single‐nucleotide polymorphism (SNP) array, a first tool for GWA mapping in potato became available. Thirty‐six tetraploid varieties and eight diploid breeding clones were genotyped for 8303 SNPs using this array. The objectives of our study were to examine in this set of germplasm: (i) the degree of polymorphism of the SolCAP SNPs in European germplasm, (ii) the population structure, (iii) temporal trends of genetic diversity and (iv) the genome‐wide extent of linkage disequilibrium (LD). Three‐quarters of the SNPs were polymorphic. In the principal coordinate analysis, a clear separation of tetraploid from diploid genotypes was observed, whereas no distinct subgroups among the tetraploid varieties were detected. The nonlinear trendline of the LD measure <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3xdsxcnr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />r2</alternatives> vs. the physical map distance decayed within 275 bp to an <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3xdsxcp9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />r2</alternatives> value of 0.10, indicating that theoretically, about 3 million equally distributed SNPs are required for GWA mapping in this diverse set of germplasm. As the LD decay changes with the population selected for GWA mapping, the number of required markers might be different in other germplasm.